Resilience in 3rd grade Muhammadiyah Vocational High School students: The impact of achievement emotions - Bangun, Tri Dewi Tunggal; Agustiningsih, Rika Dwi; Husnaini, Rovi (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
Third-year students at Vocational High School must meet many academic demands towards the end of their study period. These include fieldwork practices, report writing, attending sessions, taking tests, and preparing for exams and higher education. Such demands can affect their emotions and resilience, leading to a study being conducted to assess the impact of achievement emotions on their resilience. The research method employed in this study was quantitative, using a simple linear regression analysis technique. The research sample consisted of 183 third-grade students from SMK Muhammadiyah in Bandung, selected using a cluster random sampling technique. The study utilized two measuring tools: the achievement emotions scale and the resilience scale. The data collection method was a questionnaire, which was conducted both online and offline (paper-based). The results indicated that positive and negative emotions simultaneously influence the resilience of grade 3 vocational school students. Positive emotions play a significant positive role in increasing resilience, while negative emotions can reduce it. Educators and parents can focus on nurturing positive emotions in their students to create a positive learning environment. Cognitive restructuring may be the intervention strategy to change students' appraisal of learning situations so that they evoke enjoyment and relief and then eliminate boredom, making students more resilient.